Pediatric clonidine poisoning - Dipti Sanklecha; Praveen Palyam Nagendra; Basavaraja Gangasamudra Veerappa; Keshavamurthy Mysore Lakshmikantha (Wolters Kluwer Medknow Publications, 2021)
Clonidine, a commonly used anti-hypertensive agent, is being increasingly used in the treatment of pediatric behavioral disorders, thus increasing the incidence of pediatric poisoning. Poisoning causes somnolence, respiratory depression, hypotension, sinus bradycardia, and miosis. Clonidine overdose of >0.01 mg/kg causes bradycardia and hypotension and >0.02 mg/kg causes apnea and respiratory depression. A 13-year-old boy presented to us with ingestion of 0.073 mg/kg clonidine. He had only sinus bradycardia and drowsiness, which had resolved without any active interventions. As the life-threatening side effects of clonidine poisoning seem to be very rare even at toxic doses, it can be used safely in the pediatric age group.